2020
DOI: 10.1093/ntr/ntaa121
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevalence and COVID-19 in Europe

Abstract: Abstract Introduction This ecological study investigates the association between smoking prevalence and COVID-19 occurrence and mortality in 38 European nations as of 30th May 2020. Methods Data were collected from Our World in Data. Regression analysis was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
63
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 13 publications
10
63
3
1
Order By: Relevance
“…Berlin and Thomas also stated that “none of 20 the included papers reported on biochemical verification of smoking status”. We agree with this assessment and consider that it would be very interesting to include it (biochemical verification and COVID-19) in future reviews when these data are available, especially when most recent studies indicate a negative association between smoking prevalence and occurrence of COVID-19 at the population level in 38 European countries [ 9 ].…”
mentioning
confidence: 53%
“…Berlin and Thomas also stated that “none of 20 the included papers reported on biochemical verification of smoking status”. We agree with this assessment and consider that it would be very interesting to include it (biochemical verification and COVID-19) in future reviews when these data are available, especially when most recent studies indicate a negative association between smoking prevalence and occurrence of COVID-19 at the population level in 38 European countries [ 9 ].…”
mentioning
confidence: 53%
“…The second issue is the potential of missing other important confounding factors (e.g. obesity levels, smoking prevalence 8 ), which could be correlated with the variables of this study. Their omission could cause the estimated coefficients of this study to be biased.…”
mentioning
confidence: 99%
“…Indeed, we have recently shown that Nicotine exposure induces rapid and long-lasting increase in gene expression and protein level of ACE2 in low ACE2-expressing human pulmonary adenocarcinoma A549 epithelial cell line, which in turn translates into increased competence for SARS-CoV-2 replication and cytopathic effect [47].Different epidemiological investigations on relationship between smoking (or nicotine) and SARS-CoV-2 have been published or are available as pre-print, and we have recently extensively reviewed these data [48]. Evidence from these studies is somehow contrasting, and the role of tobacco smoking or vaping is still to be assessed [49][50][51][52][53][54][55][56][57][58][59][60]. It is possible to suppose the presence of underreporting or misreporting data in recording smoking history at admission, especially to ICU, during the COVID-19 outbreak, when the hospitals are overwhelmed.…”
Section: Physical Characteristicsmentioning
confidence: 99%